The reliability of weight-for-length/height Z scores in children. - Mwangome, M; Berkley, J (2014)
The World Health Organisation (WHO) recommends weight-for-length/height (WFL/H), represented as a Z score for diagnosing acute malnutrition among children aged 0 to 60 months. Under controlled conditions, weight, height and length measurements have high degree of reliability. However, the reliability when combined into a WFL/H Z score, in all settings is unclear. We conducted a systematic review of published studies assessing the reliability of WFL/Hz on PubMed and Google scholar. Studies were included if they presented reliability scores for the derived index of WFL/Hz, for children under 5 years. Meta-analysis was conducted for a pooled estimate of reliability overall, and for children above and below 24 months old. Twenty six studies on reliability of anthropometry were identified but only three, all community-based studies, reported reliability scores for WFL/Hz. The overall pooled intra-class correlation coefficient (ICC) estimate for WFL/Hz among children aged 0 to 60 months was 0.81 (95% CI 0.64 to 0.99). Among children aged less than 24 months the pooled ICC estimate from two studies was 0.72 (95% CI 0.67 to 0.77) while the estimate reported for children above 24 months from one study was 0.97 (95% CI 0.97 to 0.99). Although WFL/Hz is recommended for diagnosis of acute under nutrition among children below 5 years, information on its reliability in all settings is sparse. In community settings, reliability of WFL/Hz is considerably lower than for absolute measures of weight and length/height, especially in younger children. The reliability of WFL/Hz needs further evaluation.